2013
DOI: 10.1016/j.jcv.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HIV-1 and/or HIV-2 infection and CD4 count on cervical HPV DNA detection in women from Senegal, West Africa

Abstract: Background HIV infection is associated with greater risk of precancerous lesions and cervical cancer in women. However, several factors remain unclarified regarding the association between HIV infection and HPV detection, especially among those with HIV type 2 versus type 1 infection and severely immunocompromised persons. Objectives To evaluate HPV overall and type-specific detection among HIV-infected and uninfected women in Senegal. Study Design Detection of HPV DNA for 38 genotypes in cervical swabs us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 53 publications
4
26
3
Order By: Relevance
“…The percentage of HIV‐positive patients on ART has increased significantly in recent years, and in 2015 the percentage was 79% . HIV‐positive women on ART and with a normal CD4 count had a decreased risk of being infected with HPV and being diagnosed with SILs, which is consistent with previous studies . Still, the prevalence of HPV was higher in the group of well‐treated HIV‐positive women compared with the HIV‐negative women.…”
Section: Discussionsupporting
confidence: 89%
“…The percentage of HIV‐positive patients on ART has increased significantly in recent years, and in 2015 the percentage was 79% . HIV‐positive women on ART and with a normal CD4 count had a decreased risk of being infected with HPV and being diagnosed with SILs, which is consistent with previous studies . Still, the prevalence of HPV was higher in the group of well‐treated HIV‐positive women compared with the HIV‐negative women.…”
Section: Discussionsupporting
confidence: 89%
“…The results of some studies suggests that HIV infection is a known risk factor for HPV infection [27]. In our study, we found an association between HIV and HPV infection and this association remained statistically significant when we examined the association between HIV and different categories of HPV.…”
Section: Discussionsupporting
confidence: 74%
“…In the Chinese setting, we recommend three actionable measures. First, early initiation of antiretroviral therapy for HIV and improvement of treatment adherence will be effective in reversing the depletion of CD4 T cells, and decrease the likelihood of HPV infection and prevent HPV-related anal and cervical cancers in the long term 58. Second, HPV vaccination has already been shown to be immunogenic and cost-effective in women,59 60 PLHIV and MSM61–63 in many countries.…”
Section: Discussionmentioning
confidence: 99%